The experiences of children and young people with complex needs being cared for away from home: a cross-border study - Kirsten Stalker; Charlotte MacDonald; Rena Phillips; John Carpenter (Scottish Journal of Residential Child Care)
This paper reports some key findings from a two year study, commissioned by the Joseph Rowntree Foundation, which focused on children with complex needsbeing cared for away from home for one month or longer. Morris (1995), in a review of policy and research concerning disabled children living away from their families, concluded that these young people experienced 'patterns of care which would never be tolerated for non-disabled children' (Morris, 1995, p.89). She suggested that a major barrier to meeting these children's needs lies in the hidden nature of their experiences, with little information available about who they are and what their lives are like.